Covid-19 Affirms Philosophy Identity - Yeremias Jena (Center for Philosophy and Ethics, 2020)
On the world philosophy day (World Philosophy Day) which is celebrated on 19 and 20 November 2020, UNESCO invites all activists and lovers of philosophy to pay attention to the importance of philosophical thinking in helping humans face the challenges posed by the Covid-19 outbreak. Various activities such as interviews with philosophers, round table discussions, and webinars were held with a focus on the importance of philosophical thinking or reflection, and this affirms the role of philosophy in human life (UNESCO, 2020).